HUBUNGAN KETUBAN PECAH DINI DENGAN PERSALINAN SECTIO CAESAREA DI RUMAH SAKIT BUDI KEMULIAAN KOTA BATAM - Prihadianto, Dino Gagah; Kusumawardani, Erika; Riski, M. Reza (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Premature rupture of membranes (KPD) is the rupture of the amniotic membrane before there are signs of labor and after one hour is not followed by labor. Sectio caesarea (SC) or cesarean section is a surgical procedure to remove the fetus through an incision or action on the uterine and abdominal walls, provided that the fetus is healthy and weighs more than 500 grams. The purpose of this study was to determine the relationship between premature rupture of membranes and cesarean section delivery. Methods: This type of research is quantitative using observational analytic research design, with a cross sectional approach. The population in this study was the medical record data of patients with maternity pathology or with inpatient complication with simple random sampling. The results of the study were analyzed by the chi-square test. Results: There were 49 mothers diagnosed with premature rupture of membranes with sectio caesarean delivery with an expected value of (42.6%) with mothers who experienced premature rupture of membranes who performed sectio caesarean delivery and 23 mothers with an expected value of (20%) who experienced premature rupture of membranes and did not perform sectio caesarean delivery. The results of the study obtained a P-Value of 0.002 <0.05. Conclusion: There is a significant relationship between premature rupture of membranes and cesarean section delivery at Budi Kemuliaan Hospital, Batam City in 2022.